Peran Agen Pastoral Dalam Pengawasan Pemuda Katolik Paroki Santo Klemens Puruk Cahu - Haris haman; Jacob jairus (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2024)
The problems faced by adolescents at home are problems between adolescents and their parents or vice versa, problems between parents and children (teenagers). Parents are examples and role models for children (teenagers). To be an example for children (teenagers) parents must be able to build a harmonious attitude in the family, and instill religious values not only through words but what children (teenagers) need most, namely concrete actions. That is why the role of parents in the family is very important. Because following the times, the challenges are getting tougher and advanced as well. Parents are required to understand the flow of the times, to master as much as possible to help children (teenagers) lead a life on the right and right path. Parents should not neglect the education and guidance of their children, because of the busyness and demands of work. Two things that are equally heavy, equally important and equally valuable for family happiness.